ARABIC LANGUAGE ACQUISITION FOR CHILDREN OF TEACHERS AT THE PONDOK PESANTREN DARUSSALAM PARMERAAN - Nst, Mangsur; Rusdi; Efendi, Aprijon`; Halomoan (Information Technology Education Department, 2025)
Second language acquisition in early childhood is interesting to study. The purpose of this study was to determine the Arabic language acquisition ability of teachers' children at the Darussalam Parmeraan Islamic Boarding School, to find out the problems faced by teachers' children in learning Arabic as a second language at the Darussalam Parmeraan Islamic Boarding School, and to find out solutions to difficulties in learning Arabic as a second language at the Darussalam Parmeraan Islamic Boarding School. The research method used is qualitative and descriptive research using case studies. The data collection methods used are observation, interviews, and documents, and the data analysis methods used are data collection, data reduction, data presentation, and concluding. The results of this study indicate that the methods used in the learning process at the Darussalam Parmeraan Islamic Boarding School include direct methods, audio-lingual methods, presentation methods, and question-and-answer methods. The learning media teachers use are appropriate and interesting for children, such as pictures, paintings, picture books, games, and audio visuals. The difficulties experienced by children are easily forgetting the vocabulary that has been taught, and children have difficulty pronouncing letters and vocabulary, pronouncing